Report on the use of experimental statistics applied to research in an area of the Amazon Region - Fidelis , Iraci; Januário , Graciele da Silva; Batista , Patrício Ferreira (Seven Editora, 2024)
We understand that the act of research is essential in the learning process and, mainly, in the construction of autonomous and critical individuals. Understanding the appropriate use of statistics leads to fewer errors in reporting results and interpreting conclusions. What we observe today are analyzes of poorly performed experiments and erroneously interpreted results. This justifies that the student himself, when constructing his article, is capable of carrying out the analyzes and interpreting the results. The project was developed with two students from the third period of the Higher Aquaculture Technology Course at the Federal Institute of Roraima. This work aimed to make students aware of the application of designs used in agricultural experimentation and their applications, through solving a list of exercises and to present the SISVAR computer system with diverse applications in the statistical analysis of experiments, due to its ease of access and use. The students were able to use data obtained from practical examples to: suggest the best design for each exercise, analyze the data and see if they followed the assumptions for carrying out the analysis of variance, formulate hypotheses for the validity of the F test, perform the analysis of variance and apply the F test. Using the F test, they were able to carry out the study of splits and find the best treatment in each exercise based on the Tukey test study or based on the regression study. We concluded that the students acquired the ability to interpret, analyze and resolve the information arising from the data collected during the research and made them aware of the different aspects of applying statistical methods proposed in the project. DOI:https://doi.org/10.56238/sevened2023.001-008